The Use of GeoGebra in Teaching Mathematical Concepts: Practices, Barriers, and Teachers' Perceptions - Luis Dubarbie-Fernández; Álvaro Barreras; Antonio M. Oller-Marcén (Revista Latinoamericana de Tecnología Educativa)
The use of GeoGebra in teaching mathematics has grown significantly in recent years, so this study aims to explore the use of this software by teachers in teaching the limit of a function. For this purpose, a questionnaire has been designed and validated and has been answered by 129 mathematics teachers. The data have been analyzed both quantitatively and qualitatively with the objective of knowing obstacles to the use of GeoGebra and to the development of own applets, to identify the most outstanding characteristics of the GeoGebra applets for teaching the limit and to determine the moments of the process of teaching-learning in which this tool is used. Thus, a limited use of GeoGebra in teaching the limit and a very low percentage of teachers who develop their own applets has been identified, mainly due to the absence of technological resources and the lack of knowledge. Furthermore, interactivity and the possibility of using various representation systems of the limit are revealed as the characteristics most valued by teachers. Finally, GeoGebra is especially used when showing examples and barely used in the evaluation process.